The Ecological Architecture Approach Analysis at Kusuma Agrotourism Resort & Convention Hotel - Fajar Mahendra Nurzein; Muchlisiniyati Safeyah (CV. Publikasi Indonesia, 2024)
Resort areas are popular recreational destinations for urban populations, but rapid urban development often leads to significant environmental degradation in these areas. This degradation is evidenced by the decline in water, air, and soil quality, the extinction of local flora and fauna, and the destruction of natural ecosystems. As a response, the application of ecological architecture has become essential in designing and constructing city facilities, including resorts, to mitigate environmental damage. This study aims to examine the implementation of various principles of ecological architecture in resort areas and identify sustainable materials suitable for such applications. A qualitative descriptive method is employed, combining literature reviews and field observations to analyze the integration of ecological architectural principles in the resort area. The findings reveal that key principles such as the use of local materials, energy-efficient systems, and environmental management strategies have been applied. However, the study also highlights areas where improvements can be made to better preserve the ecosystem and minimize the negative impacts of architectural design.